EVALUATION OF NUTRIENT MANAGEMENT OPTIONS FOR RICE-POTATO-WHEAT CROPPING SYSTEM OF UPPER GANGETIC PLAIN REGION - K. Shukla, Arvind; Khan, M. A.; Upadhayay, N. C; Singh, O. P. (Potato Journal, 2013)
In order to evaluate nutrient management options for rice-potato-wheat system, a field experiment was conducted in Typic Ustochrept at CPRI Campus, Modipuram. Among the seven treatment options tested, the yield of individual crop as well as potato equivalent yield was highest where 100% NPK were supplied through inorganic fertilizers. The treatment receiving recommended NPK along with secondary nutrient (Zn and S) did not show an edge over 100% NPK only. Depending upon the crops, the treatment where 100% NPK were supplied through organic manures gave 40-85% lower yield as compared to treatment receiving 100% recommended NPK through inorganic fertilizers. The organic carbon content has also increased in most of the treatments except in control. As compared to inorganic, the NO3-N content was much lower in upper layer of profile in organic treatment.